2011
DOI: 10.1111/j.1464-5491.2011.03282.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived challenges and priorities in co‐morbidity management of older patients with Type 2 diabetes

Abstract: Aims To explore older patients’ perceived impact of chronic co-morbid conditions on Type 2 diabetes self-management. Methods We used purposive sampling to select 32 mentally alert community-dwelling adults, aged 60 years or older, diagnosed with Type 2 diabetes and at least one other chronic health condition to participate in focus groups. We summarized the discussions following each focus group and identified codes to describe the overarching themes. Results We conducted eight 90-min focus groups, each co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 20 publications
3
92
0
Order By: Relevance
“…In these qualitative studies, patients described a limited capacity to manage their multiple health conditions due to a diminished ability to recognize signs and symptoms of an exacerbating condition, difficulty managing complex medication regimens, and confusion resulting from conflicting self-care treatment recommendations [66][67][68]. Further, these studies found patients frequently prioritized the management of one health condition over another.…”
Section: Complications and Comorbiditiesmentioning
confidence: 92%
See 1 more Smart Citation
“…In these qualitative studies, patients described a limited capacity to manage their multiple health conditions due to a diminished ability to recognize signs and symptoms of an exacerbating condition, difficulty managing complex medication regimens, and confusion resulting from conflicting self-care treatment recommendations [66][67][68]. Further, these studies found patients frequently prioritized the management of one health condition over another.…”
Section: Complications and Comorbiditiesmentioning
confidence: 92%
“…Several studies have explored the impact of multiple diabetes complications and comorbidities on patients' selfcare and quality of life [66][67][68]. In these qualitative studies, patients described a limited capacity to manage their multiple health conditions due to a diminished ability to recognize signs and symptoms of an exacerbating condition, difficulty managing complex medication regimens, and confusion resulting from conflicting self-care treatment recommendations [66][67][68].…”
Section: Complications and Comorbiditiesmentioning
confidence: 98%
“…Multimorbidity, "the most common chronic condition experienced by adults", places significant demands on individuals, clinicians and the health system (25). Individuals must navigate an illness trajectory complicated by processes of adaption and re-adaption linked to each subsequent diagnosis (135,182,194 Research investigating the experience of managing multiple chronic conditions has grown in prominence in recent years, as an increasing number of largely qualitative studies have examined the challenges people face (133,135,(195)(196)(197)(198) Treatment burden arises from the need to learn about treatments, attend medical appointments, undergo tests or examinations, and adhere to complex medication and self-care regimens (95,199,201,202). For those managing multiple chronic conditions these demands are amplified in the face of unwanted complications and complexity (73,95,202,203).…”
Section: Multiple Conditions: the Patient Experiencementioning
confidence: 99%
“…Looking to simplify the complexity of managing multiple chronic conditions and the resulting treatment burdens, patients must frequently prioritise conditions, goals, medications and/or outcomes (28,73,93,133,135,189,196,206,(217)(218)(219)(220)(221)(222)(223).…”
Section: Social Life Burdenmentioning
confidence: 99%
See 1 more Smart Citation